Pengembangan Media Pembelajaran Menggunakan Prezi pada Materi Tumbuhan Sumber Kehidupan di Bumi Kelas IV SD - Yufita Indriani; Abna Hidayati (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
One.of the efforts that.can.be.done.solve.problems.in the process is to develop learning media using the.right.method. One.of.thelearning.problems.found.is use of media where the teacher only uses media in the form of textbooks and videos. From YouTube, in science learning there is a lot of material that requires media in the form of pictures or videos which are equipped with sound to clarify the delivery of the material, so With the media used by the teacher, students do not understand the material being explained and students are less enthusiastic about participating in learning. Therefore this development research aims to produce valid. This research uses a type of research known as research and development (R&D). The development model used in the 10 steps of Borg and Gall is as follows: (1) Potential and Problems, (2i Data Collection, (3) Product Design, (4) Design Validation, (5) Product Testing, (6) Product Revision, (7)) Product trial, (8) Trial, and (10) Production. Learning media products will be testd for imedia validty by two ivalidators and the material ivalidity test will be carried out by one validator. The practicality test results were carried out on 18 grade IV SD UNP Laboratory Development. Validty test, it show that the imedia is said to be very invalid with an ipercentage of 95%, while the eligibility value by material experts is very ivalid with an ipercentage of 96%. At the end of the test, the media product was as very practical of 96%. It can be that learnng meda for the Science subject in class IV SD is considered practical and appropriate to use. Keywords: Learning Media, Prezi, IPAS